Psychological Well Being Wanita Pada Korban Kekerasan dalam Rumah Tangga - Salsadziba Putri Imanda; Adinda Putri; Yuarini Wahyu Pertiwi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The household must be a safe place for all family members. However, in fact, many households become places of suffering and suffering due to acts of violence. For victims of domestic violence, achieving psychological well-being can be a big challenge considering the trauma they have experienced. The aim of this research is to find out the psychological well-being of victims of domestic violence. The research method employed involves conducting library research, which involves collecting secondary data from various sources such as literature books, research findings, journals, and articles. Research shows high rates of violence, depression, anxiety and PTSD among women receiving specialist domestic violence services.